Kerimcan’ın “Bireyleşme” Yolculuğu Bağlamında Devlet Ana Romanında Arketipler - Fedai, Özlem (FSM Vakıf Üniversitesi, 2016)
Jung psikolojisinde “bireyleşme” tek, homojen bir varlık olmayı, kişinin kendisini tamamlamasını ifade eder. “Kendini gerçekleştirme” denen bu serüven, ben-merkezli ya da bireyci olmak, kolektif sorumluluklarına karşıt davranmak anlamına gelmez. Tersine bu kavram, toplumla ilişki içerisindeki bireyin ona karşı görevlerini de yerine getirerek kendi kimliğini oluşturmasıdır. Yani “bireyleşme”, bireyin yaptığı tercihlerle kendi varoluşunu tamamlaması anlamına gelir. Bu çalışmada Kemal Tahir’in Devlet Ana romanının kahramanlarından Kerimcan’ın, “bireyleşme” yolculuğu üzerinde durulmuştur. Kerimcan’ın tercihleri neticesinde ulaştığı bireyleşme süreci, Jung’un “bireyleşme yolculuğu” üzerine yaptığı çalışmalarından hareketle ele alınmıştır. Çalışmada Jung’un “aşama/ben” arketipi başta olmak üzere işaret ettiği arketipler üzerinde durulmuş; böylece 13. yy Osmanlı toplumunda kolektif zorunlulukların bireyleşme yolculuğu üzerinde oldukça etkili olduğu ancak bireyin kendini gerçekleştirmesine engel olmadığı sonucuna varılmıştır.

In the psychology of Jung, the concept of individuation refers to being a homogenous entity, the self-completion of the individuals’. This adventure called as “self-realization” is not equivalent to being self-centered, individualistic or acting opposite to the collective responsibilities. Rather, this concept means to the creation of the individuals’ own identities, by also fulfilling their duties towards the society. In other words, individuation refers to the formation of individuals’ their existence by their own choices.In this study, the individuation journey of the main character in Kemal Tahir’s novel Devlet Ana is examined. The individuation journey of Kerimcan that was shaped through his own choices is under debate by focusing on the Jung’s works about ‘the journey of individuation’. The archetypes that was pointed by Jung, especially ‘The Self’ archetype is also examined. Therefore, this study concludes that although collective obligations in the Ottoman society of the 13th century had a great influence on the process of individuation, these obligations never hindered the individuals in their self-realization.
The Archetypes in the Novel Devlet Ana within the Context of Kerimcan’s Journey of Individuation
Keywords: Bireyleşme; Kerimcan; Devlet Ana; Arketipler; Individuation; Archetypes